Actions of FGF2, LIF, and IGF1 on bovine embryo survival and conceptus elongation following slow-rate freezing - Stoecklein, Katy S.; Garcia-Guerra, Alvaro; Duran, Benjamin J.; Prather, Randall S.; Ortega, M. Sofia (Frontiers in Animal Science, 2022)
Culture environment during in vitro embryo production can affect embryo phenotype and pregnancy outcomes, making culture modifications a logical approach for improving embryo competence. Previously, the addition of the growth factors FGF2, LIF, and IGF1, termed FLI, to the culture medium improved bovine embryo development, and re-expansion following cryopreservation. The objective of this study was to investigate the survival of cryopreserved FLI treated embryos at day 15 of pregnancy and evaluate conceptus transcriptomes. Embryos were produced using in vitro fertilization of abattoir-derived oocytes, cultured to the blastocyst stage in the presence or absence of FLI (+/- FLI), and cryopreserved by slow-rate freezing. Thawed embryos were transferred into non-lactating recipient beef cows and eight days later conceptuses were recovered and analyzed. For a subset of conceptuses whole transcriptome analysis was performed by using the NovaSeq 6000. There was no detectable difference in conceptus recovery or average conceptus length between the two groups. There were 32 differentially expressed transcripts, 23 up-regulated and nine down-regulated in the +FLI group compared to -FLI. Genes were involved in interferon signaling, prostaglandin synthesis, and placental development. This study reveals that embryos cultured with or without FLI and cryopreserved by slow-rate freezing have similar developmental competence up to day 15 of development. Nevertheless, differences in gene expression exhibit an effect of FLI on conceptus signaling during elongation.